2006
DOI: 10.1051/0004-6361:20054313
|View full text |Cite
|
Sign up to set email alerts
|

H2active jets in the near IR as a probe of protostellar evolution

Abstract: We present an in-depth near-IR analysis of a sample of H 2 outflows from young embedded sources to compare the physical properties and cooling mechanisms of the different flows. The sample comprises 23 outflows driven by Class 0 and I sources having low-intermediate luminosity.We have obtained narrow band images in H 2 2.12 µm and [Fe ii] 1.64 µm and spectroscopic observations in the range 1−2.5 µm. From [Fe ii] images we detected spots of ionized gas in ∼74% of the outflows which in some cases indicate the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
180
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(193 citation statements)
references
References 63 publications
12
180
1
Order By: Relevance
“…In general, MHEL properties are consistent with shockheated gas from the inner regions of Herbig-Haro objects or from spatially extended wide-angle winds (Davis et al 2001;Caratti o Garatti et al 2006;Beck et al 2008;Davis et al 2011). The reported gas temperatures and excitation properties of IRS54 are consistent with shock-heated material, as well.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In general, MHEL properties are consistent with shockheated gas from the inner regions of Herbig-Haro objects or from spatially extended wide-angle winds (Davis et al 2001;Caratti o Garatti et al 2006;Beck et al 2008;Davis et al 2011). The reported gas temperatures and excitation properties of IRS54 are consistent with shock-heated material, as well.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, thanks to detecting several H 2 lines, excitation diagrams could be constructed to derive the temperature, H 2 column density, and extinction of the molecular gas (e.g., Caratti o Garatti et al 2006;Garcia Lopez et al 2010). The results are shown in Table 1.…”
Section: Outflow Physics and Morphologymentioning
confidence: 99%
“…The angular resolution of this image is much (Beltrán et al 2002) overlaid with an IRAC 4.5 μm image. The H 2 emission shows a large number of molecular hydrogen features, many already found by Nisini et al (2001), Reipurth et al (2003), and Caratti o Garatti (2006), whose nomenclature we use and expand. The black crosses show the positions of the 3.1 mm sources, BIMA 1, 2, and 3 from Beltrán et al (2002), and the white one shows the position of the 1.3 mm continuum source C detected by Codella et al (2001). higher than that of Fig.…”
Section: The Title Of the Spitzer Program Is Star Formation In Brightmentioning
confidence: 72%
“…Beltrán et al (2002) have conducted a detailed study of the bipolar outflow associated with the intermediate-mass protostar BIMA 2, and shown that its complex morphology and kinematics are possibly the result of the interaction between the outflow and the dense cores surrounding the protostar. NIR images of the region have also revealed a number of small scale molecular hydrogen and Herbig-Haro (HH) flows Sugitani et al 2002a;Reipurth et al 2003;Caratti o Garatti et al 2006). This evidence of ongoing star-formation activity at the head of the cometary globule, together with the relatively proximity of the region, make IC 1396N one of the best candidates for studying potential sequential star formation.…”
Section: Introductionmentioning
confidence: 99%
“…, H 2 (see, e.g., Hartigan et al 1995;Nisini et al 2002;Caratti o Garatti et al 2006). A few YSOs, namely #2, #3, #11, and #18, also show permitted ionic emission lines (e.g., O i, Fe i, Fe ii, Na i, Mg ii, C i), which are characteristic of active young stars (see, e.g., Hamann & Persson 1992a,b;Kelly et al 1994;Hernández et al 2004), and usually associated with chromospheric activity.…”
Section: Optical and Nir Spectramentioning
confidence: 99%